Peculiarities of structural, electrokinetic, energetic, and magnetic properties semiconductive solid solution Lu1-xVxNiSb - Stadnyk, Yu.; Romaka, V.A.; Romaka, L.; Demchenko, P.; Horyn, A.; Poplavskyi, O.; Pashkevych, V.; Haraniuk, P. (Physics and Chemistry of Solid State, 2023)
The structural, electrokinetic, energetic, and magnetic properties of the new semiconductive solid solution Lu1-xVxNiSb, х=0–0.10, were studied. It was shown that V atoms could simultaneously occupy different crystallographic positions in different ratios, generating structural defects of acceptor and donor nature. This creates corresponding acceptor and donor bands in the bandgap εg of Lu1-xVxNiSb. The mechanism of the formation of two acceptor bands with different depths of occurrence has been established: a small acceptor band εА2, formed by defects due to the substitution of Ni atoms by V ones in the 4c position, and band εА1, generated by vacancies in the LuNiSb structure. The ratio of the concentrations of generated defects determines the position of the Fermi level εF and the conduction mechanisms. The investigated solid solution Lu1-xVxNiSb is a promising thermoelectric material.